Algoritma TikTok dan Pandangan Mahasiswi: Mengungkap pengaruh Filter Bubble dalam Kasus Mafia Skincare - Dewi, Recha Kusliana; Suparman, Suparman (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This study aims to examine the influence of TikTok's bubble filter algorithm on female college students' perceptions of the skincare mafia phenomenon. The research design uses a quantitative approach with linear regression analysis, this study identifies how TikTok content consumption patterns affect female college students' views on this issue. The results show that the TikTok algorithm has a significant influence in strengthening female college students' perceptions of the skincare mafia. The algorithm works by displaying content that is relevant to users' preferences, thus reinforcing preconceived views and limiting exposure to different perspectives. This research contributes to the understanding of how social media algorithms can shape perceptions and limit the diversity of information received by users.